2017
DOI: 10.1016/j.ijrobp.2016.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Ablative Radiation Therapy is Highly Safe and Effective for Elderly Patients With Early-stage Non-Small Cell Lung Cancer

Abstract: Purpose To discern the efficacy and toxicity of SABR in the elderly population (age ≥75), and to consider how it compares to surgical outcomes historically reported in the elderly. Methods and Materials 772 patients with clinically early-stage I-II NSCLC (T1-T3 N0M0) were treated with SABR (50 Gy in 4 fractions or 70 Gy in 10 fractions) between 2004-2014 at our center (n=442 age <75, n=330 age ≥75). Primary end points included overall survival, progression-free survival, and grade ≥3 toxicity. Median follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 39 publications
4
22
0
Order By: Relevance
“…Another study regarding the safety of definitive SBRT in patients more than 80 years old suggested its high efficacy and tolerability [ 11 ]. Of interest, a prior study that investigated the effectiveness of SBRT at a single center reported that the OS rates for patients over 75 years were 86% at 1 year, 57.5% at 3 years, and 39.5% at 5 years [ 22 ], which is comparable to the survival rates of 79.1% at 1 year, 61.3% at 3 years, and 32.4% at 5 years in our patients who underwent SBRT.…”
Section: Discussionsupporting
confidence: 67%
“…Another study regarding the safety of definitive SBRT in patients more than 80 years old suggested its high efficacy and tolerability [ 11 ]. Of interest, a prior study that investigated the effectiveness of SBRT at a single center reported that the OS rates for patients over 75 years were 86% at 1 year, 57.5% at 3 years, and 39.5% at 5 years [ 22 ], which is comparable to the survival rates of 79.1% at 1 year, 61.3% at 3 years, and 32.4% at 5 years in our patients who underwent SBRT.…”
Section: Discussionsupporting
confidence: 67%
“…Particularly for elderly patients, SBRT's effectiveness based on lung cancer-specific survival and progression-free survival is the same in the elderly (>75 years old) as it is the average age population (<75 years old). SBRT is well tolerated with a low risk of toxicity (3). Compared to historical outcomes with surgery in the elderly, SBRT outcome is considered comparable for stage I disease but has less morbidity (3).…”
Section: Rt-treatment For Local Controlmentioning
confidence: 99%
“…SBRT is well tolerated with a low risk of toxicity (3). Compared to historical outcomes with surgery in the elderly, SBRT outcome is considered comparable for stage I disease but has less morbidity (3).…”
Section: Rt-treatment For Local Controlmentioning
confidence: 99%
“…Stereotactic body radiation therapy (SBRT) is the usual treatment for medically inoperable patients, and it provides good local control rates and induces minimal toxicity [ 6 11 ]. Therefore, SBRT may be beneficial in elderly patients.…”
Section: Introductionmentioning
confidence: 99%